Analisis Faktor Determinan Kinerja Bidan dalam Pelaksanaan Asuhan Persalinan Normal di Kabupaten Merangin Tahun 2019 - Dian Mayasari; Hardisman Hardisman; Desmiwarti Desmiwarti (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Based on health profile of Jambi Province (2015)  NLC coverage by health worker in Merangin district health has not reached the target. It shows the macro performance of midwives in the village is not optimal. Some factors related to the performance of a healthcare worker in providing health services are: Individual variables, psychological variables and organizational variables. The purpose of this research is to analyze the factors determinant of the performance of midwives in the implementation of  in Merangin year 2018.This type of research is analytic observation with cross sectional approach, this research has been conducted in the work area of Merangin District Health Office February until August 2019, with the population of all midwives in the district Merangin as much as 608 people. The number of samples was 83 people taken with simple random sampling technique. Bivariate analysis using Chi Square test and multivariate analysis using binary logistic regression. The results of the study there was a level of knowledge relationship (p= 0,000; OR:10,879; 95 % CI;3,832-30,8850) and the experience of midwives (p= 0,000; OR:10,879; 95 % CI;3,832-30,8850) with the performance of midwives in the implementation of the NLC, no perceptual relationship about the award (P = 0,991), attitude (P = 0,351), perception of the NLC equipment (p = 0,261), Midwives  Training (0,660) with the performance of midwives in the implementation of  NLC in Merangin Regency and the most influential factor with the performance of midwives in the implementation of NLC in Merangin District namely the level of knowledge of. Advised to the midwives more update information about the NLC to improve the knowledge of midwives in the NLC.